Developing & Designing Smart City Profiling Framework - Sri Winarno; Indra Gamayanto; Asih Rohmani (Universitas Sriwijaya, 2022)
A smart city is a change in the pattern of life, wherein seeing the concept of smart city, we must focus on one side or several sides but must see the bigger picture so that the definition of a smart city can create precisely. This article developed from previously article such as smart city articles 1.0-5.0 and then developed into three final concepts regarding the smart city. These three concepts consist of the smart city profiling framework, innovation profiling, and the seven stages of smart city profiling (the maturity level of smart city profiling). The focus of the problems to be developed can see in the smart city profiling framework which divides into six important parts: social profiling, BMM (Business model mapping) 101 framework, innovation profiling, social media profiling, culture profiling and education profiling. These six parts cannot be separated from each other and must build together. Therefore, this article will focus on completing the concept of smart city profiling, so that a strong foundation will create in implementing smart city. The method contained in the smart city 5.0 framework and the framework developed to be more advanced. The result of this article is a smart city profiling framework and a more detailed concept. Although the maturity level table shows, the discussion will complete in the next article and innovation profiling.